Mecp2 deficiency induces dysphagia in a preclinical model of Rett syndrome - Luiz Marcelo Oliveira; Maryam Saeed Aslam; Jan-Marino Ramirez; Alyssa D. Huff (Proceedings of the National Academy of Sciences, 2026)
Rett syndrome is an x-linked genetic neurological disorder primarily caused by mutations in the methyl-CpG-binding protein 2 (MECP2) gene. This progressive neurodevelopmental condition hinders patients’ ability to breathe and eat normally. It remains unclear how Mecp2 deficiency leads to the high prevalence of dysphagia and aspiration pneumonia observed in individuals with Rett syndrome. This study aims to determine the effects of Mecp2 deficiency on swallow-related neuromuscular mechanisms that contribute to dysphagia in Rett syndrome. Swallow-related submental complex duration and amplitude were significantly decreased in both Mecp2 −/y and Mecp2 +/− mice compared to wild-type, likely due to reduced motor unit activation. In Mecp2- deficient mice, cholinergic immunoreactivity in the hypoglossal, facial, and trigeminal motor nuclei was decreased in postsymptomatic, but not presymptomatic mice. We also observed a significant increase in the transition time from inspiration to swallow, swallow to the subsequent inspiration, and impaired post swallow respiratory rhythm resumption in Mecp2 −/y , but not Mecp2 +/− mice. The combination of decreased ChAT + cells in brainstem motor nuclei and reduced submental muscle complex activity suggest impaired swallow-related hyolaryngeal elevation and laryngeal vestibular closure. These results provide insight into a neuromuscular mechanism underlying dysphagia in Rett syndrome and support the use of Mecp2- deficient mice as a viable preclinical model for further investigation of swallow and upper airway dysfunction in Rett syndrome.